Biodegradable composites of poly(butylene succinate‐co‐butylene adipate) reinforced by poly(lactic acid) fibers. Issue 25 (12th March 2016) - Meng, Linghan; Gao, Chengcheng; Yu, Long; Simon, George P; Liu, Hongsheng; Chen, Ling
ABSTRACT: Biodegradable composites of poly(butylene succinate‐ co ‐butylene adipate) (PBSA) reinforced by poly(lactic acid) (PLA) fibers were developed by hot compression and characterized by Scanning electron microscopy (SEM), differential scanning calorimetry (DSC), dynamic mechanical analyzer, and tensile testing. The results show that PBSA and PLA are immiscible, but their interface can be improved by processing conditions. In particular, their interface and the resulting mechanical properties strongly depend on processing temperature. When the temperature is below 120 °C, the bound between PBSA and PLA fiber is weak, which results in lower tensile modulus and strength. When the processing temperature is higher (greater than 160 °C), the relaxation of polymer chain destroyed the molecular orientation microstructure of the PLA fiber, which results in weakening mechanical properties of the fiber then weakening reinforcement function. Both tensile modulus and strength of the composites increased significantly, in particular for the materials reinforced by long fiber. © 2016 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2016, 133, 43530. Abstract :